Leuconostoc mesenteroides SJRP55: a potential probiotic strain isolated from Brazilian water buffalo mozzarella cheese - De Paula, Aline Teodoro [UNESP]; Jeronymo-Ceneviva, Ana Beatriz [UNESP]; Silva, Luana Faria [UNESP]; Todorov, Svetoslav Dimitrov; Franco, Bernadette Dora G. Mello; Penna, Ana Lúcia Barretto [UNESP] (Springer Nature, 2014)
The probiotic potential of Leuconostoc mesenteroides subsp. mesenteroides SJRP55 isolated from water buffalo mozzarella cheese was evaluated. The microorganism presented resistance to stressful conditions that simulated the gastrointestinal tract, and to the best of our knowledge Leuconostoc mesenteroides SJRP55 was the first of this species with the ability to deconjugate bile salts. Tolerance to NaCl was temperature dependent, as well the results obtained by aggregation capacity. The strain presented good adhesion properties, β galactosidase activity, viability in fermented milk during storage, non-active against Streptococcus thermophilus and sensible to most of the tested antibiotics. Some analgesic medications inhibited the growth of the strain. Leuconostoc mesenteroides SJRP55 exhibited in vitro probiotic potential, and it can be better characterized through future in vivo tests. This bacterium presents higher functional properties compared to other studied strains, and therefore it is a potential candidate for the application as a probiotic strain, which could be used by industries in the manufacture of functional milk-based products.
Keywords: Lactic acid bacteria; Therapeutical; characteristics; Aggregation; Bile salts; Adhesion properties; Fermented milk; bacteria lática; propriedade funcional; agregação; sais biliares; propriedade de adesão; leite fermentado